The Limits of Prudential Supervision: Economic Problems, Institutional Failure and Competence - Bernard Shull (Levy Economics Institute of Bard College, 1993)
Bank supervision typically receives little if any attention when banks are operating without difficulty. But when banks fail in large numbers, or large banks fail, and the system itself is threatened, supervision becomes a focal point for criticism and reform (see, for example, Conference Report, 1998, Title I, IX; Pecchioli, 1987, pp. 11 ff.; and Comptroller General of the U.S., 1977). On such occasions, institutional changes may take equal billing with the "improvement" of supervision. But as often as not, the only thing Congress can agree on is that supervision needs to be better. This usually translates into more supervisors operating with more authority. The repeated augmentation of bank supervision may give the impression that it is a solution rather that a symptom of recurring banking problems; and it is in the interest of supervisors to suggest that this is the case. Repeated disappointments about past performances never seem to undermine the promise that more and better supervisors, with more authority, will make things better in the future. The historical record suggests that this is not true. There are, however, independent reasons for questioning whether, in and of itself, more supervisors with more restrictive authority will help very much. It is argued below that the promise of supervisory enhancement is an illusion traceable to the belief that ignores the limitations of supervision in dealing with the problems that actually exist. These limitations include: (1) the existence of an intractable economic problem confronting depository institutions; (2) at least two distinct institutional failures, a fragmented regulatory system composed of multiple agencies and the growth of opportunism among banking organizations, that make it difficult to formulate and implement appropriate policies; and, finally, (3) the inability of the existing supervisory establishment to deal with these economic and structural issues. The nature of supervision is discussed. The limitations are reviewed in Section III, and the inadequacy of the current supervisory establishment to deal with the problems it must deal with to be successful is considered in Section IV. Some proposals to remedy the existing difficulties are presented in Section V. These include the consolidation of the "stand-alone" supervisory agencies with the monetary authority.
Keywords: 330